(untitled) (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. Introduzione - 2. Il caso della minoranza uigura come caso studio, tra identità etnico-religiosa, violazioni dei diritti umani e misure di contrasto all’epidemia di Covid-19 - 3. (segue) in particolare, il problema dei campi d’internamento nello Xinjiang e l’epidemia di Covid-19 - 4. Il contrasto tra le norme internazionali sui diritti umani e le misure adottate nei confronti della minoranza uigura: in particolare, il problema dei campi d’internamento - 5. Il contrasto tra le norme internazionali in materia di diritto alla salute e lotta alle pandemie e le misure adottate nello Xinjiang in tempi di Covid-19 - 6. Conclusioni. Ethnic-religious minorities in times of Covid-19: China and the Uighur minority, between violations of human rights and violations of the right to health ABSTRACT: The recent outbreak of Covid-19 that originated in China, has brought the matter of state sponsored persecution of the Uighur minority in Xinjiang to the attention of the international community. The problem of discrimination and persecution of such ethno-religious minority is not new. However, the spread of epidemic, has represented an opportunity for the Chinese national authorities to tighten the measures which have long been adopted against the Uighur minority. This paper aims at highlighting the great impact Covid-19 has had on the repression of Uighur minority since it has led to a dramatic escalation of the systematic violation of human rights which includes not only mass detention in internment camps but also the violation of other fundamental human rights such as the right to health and to access healthcare